Differences in Blood and Milk Fatty Acid Profile of Primiparous and Multiparous Mediterranean Buffaloes Cows During Transition Period and Early Lactation - Verdurico, Lenita Camargo; Gandra, Jefferson Rodrigues; Takiya, Caio Seiti; Junior, Jose Esler de Freitas; Barletta, Rafael Villela; Gardinal, Rodrigo; Calomeni, Gustavo Delfino; Gomes de Paiva, Pablo; Rennó, Francisco Palma (Journal of Buffalo Science, 2015)
The objective of this study was to determine the differences in blood and fatty acid (FA) profile between primiparous and multiparous Mediterranean buffaloes cows from 28 days of expected calving date until 56 days in milk. Nine multiparous (MUL) and 7 primiparous (PRI) cows were used in the present study, animals grazed in Brachiaria decumbens and supplemented with 2.0 kg of concentrate/day. Blood and milk samples were collected once a week and data were submitted to repeated measures analysis using PROC MIXED of SAS. Multiparous cows presented higher concentrations of glucose and non-esterified FA during pre- and post-partum period, higher cholesterol during post-partum when compared to PRI. Milk yield and fat content were higher for MUL (6.44 kg/d and 7.89%) when compared to PRI (5.66 kg/d and 6.75%). Palmitic and palmitoleic FA were lower and C18:0, C18:1 trans-11 and C18:1 cis-9 FAwere higher in MUL cows. Multiparous buffalo cows demonstrated higher milk yield and fat content than PRI, and milk FA profile of MUL had higher amounts of C18:0 FA. Multiparous buffalos presented higher non-esterified fatty acid, which altered milk fat content, and higher milk yield than primiparous cows. Furthermore, multiparous cows presented a higher content of FA from incomplete biohydrogenation process.